Gambaran Positive Parenting pada Ibu Sambung di Samarinda - Karim, Abdul; Hayati, Afita Nur; Permatasari, Rini Fitriani (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2024)
This research is based on the high divorce rate in Samarinda City, especially in the Samarinda Ulu District. A complete family structure significantly influences the child’s growth and development process. To restore a complete family structure, a father might remarry, as the presence of a mother plays a crucial role in the family. However, many people hold negative assumptions about the presence of a stepmother. These negative assumptions are not always accurate, as many stepmothers successfully build positive and supportive relationships with their stepchildren through a positive parenting approach. The purpose of this study is to understand the role of stepmothers using the positive parenting approach by Rodrigo Byrne and Rodriguez, which consists of six aspects: nurturing, structuring, stimulation, recognition, empowerment, and being free from violence. This research employs a qualitative, phenomenological approach, with data collection techniques including interviews and documentation. The findings reveal that stepmothers show affection and care, establish clear rules and routines with consistent implementation, support the intellectual and creative development of children, appreciate children’s achievements by giving praise, provide responsibilities to encourage independence and self-confidence, and engage in open communication whether or not conflict is present. These approaches demonstrate the commitment of stepmothers to creating an environment that supports the positive development of their stepchildren.